Characterization of Zanthoxylum rhoifolium (Sapindales: Rutaceae) Essential Oil Nanospheres and Insecticidal Effects to Bemisia tabaci (Sternorrhyncha: Aleyrodidae) - Karla de Castro Pereira (Plants, 2022)
Encapsulation via nanotechnology offers a potential method to overcome limited thermal and photo-stability of botanical pesticides. In this study, nanospheres of essential oils (NSEO) derived from Zanthoxylum rhoifolium Lam. fruit were characterized and evaluated for their photostability and insecticidal activity against Bemisia tabaci. Three major compounds of Z. rhoifolium fruits were detected by CG-MS: β-phellandrene (76.8%), β-myrcene (9.6%), and germacrene D (8.3%). The nanoprecipitation method was used to obtain homogeneous spherical NSEO, with ≥98% encapsulation efficiency. Tests with UV/Vis spectrophotometry showed significantly reduced photodegradation from exposed NSEO samples when compared with essential oil (EO) controls. Whitefly screenhouses bioassays with bean plants treated with 0.25, 0.5, 1 and 1.5% suspensions showed EO treatments in both free and nanoencapsulated forms reduced adult whitefly oviposition by up to 71%. In further tests, applications at 1.5% caused ≥64% mortality of second instar nymphs. When the test was conducted under high temperature and light radiation conditions, the insecticidal effect of NSEO treatments was improved (i.e., 84.3% mortality) when compared to the free form (64.8%). Our results indicate the insecticidal potential of EO-derived from Z. rhoifolium fruits with further formulation as nanospheres providing greater photostability and enhanced insecticidal activity against B. tabaci under adverse environmental conditions.